Comparison of Clinical outcomes of chronic disease patients between an accredited pharmacy care service versus a pharmacy care service at Klong-Sala primary care cluster of Phetchabun hospital. - Chaichumpu, Sirichai (Journal of Disease and Health Risk DPC.3, 2022)
The aim of this mixed methods study was to compare the clinical outcomes and experiences of patients with chronic diseases between an accredited pharmacy nursing service and a pharmacy nursing service in the Klong Sala Primary Care Cluster of Phetchabun Hospital. The sample consisted of sixty patients with chronic diseases treated at Klong Sala Primary Care Cluster of Phetchabun Hospital. The samples were divided into 2 groups, with each group comprising 30 patients: the group who had their medicines refilled at quality pharmacies and the group who received treatment at Klong Sala Primary Care during the same period from October 2019 to October 2020. The research consisted of quantitative studies, which retrospectively collected data on clinical outcomes, and qualitative research, which interviewed patients with chronic conditions about their experiences of using the services. Research tools included a clinical record form, a form to assess patients’ experiences of services and interview questionnaires. Data were collected between February and March 2021. Data were analyzed using software with statistical percentages, median values, Fisher exact probability test, Mann-Whitney U test and Wilcoxon signed ranks test. The statistical significance level was set at 0.05. The results showed that the clinical outcomes of patients with chronic diseases who had their medications refilled at an accredited pharmacy and from those at Klong Sala primary care were not significantly different in all outcomes, however the experience of using the medication refill service at the pharmacy was significantly higher than that of medication treatment at Klong Sala (p<0.001). In conclusion, the use of a quality pharmacy service is a service system that encourages patients with good control of chronic diseases to receive convenient services without having to use the medication service at Khlong Sala Family Doctor Clinic. Consequently, patients receive fast service, no long waiting times and continue to receive quality medicines.